Formulating a stochastic discounting model with actuarial and risk management applications - Constantinos T. Artikis (SPOUDAI - Journal of Economics and Business, 2012)
Stochastic discounting models are generally recognized as extremely strong analytical tools for a very wide variety of fundamental areas in the actuarial discipline. The paper is mainly devoted to the formulation, investigation and application in the actuarial discipline of a stochastic discounting model. It is shown that the formulated stochastic discounting model can substantially support the role of proactivity in making insurance decisions.
Keywords: C51; 330; Stochastic Discounting; Risk Management; Model